Cross-Disciplinary Exploration and Application of Reflection as a High Impact Pedagogy - Sarah E. Summers, PhD; Heather C.S. Chenette, PhD; Ella L. Ingram, PhD; Jay P. McCormack, PhD; Patrick J. Cunningham, PhD (Park University, 2016)
Reflection is a high-impact practice in education. This paper explores the premise, approach, and outcomes of a learning community centered on scholarly engagement with the literature of reflection. Using the reflection model operationalized by a national consortium, we developed, implemented, and assessed reflection activities designed to create opportunities for transfer of skills and conceptual change. Two case studies reveal commonalities in using reflection in a college setting. We explore the questions that emerged as a result of our experiences, and connect this work to the importance of engaging with colleagues in a community of learners.